Assessment of parental stress using the "Eltern-Belastungs-Screening zur Kindeswohlgefährdung" (EBSK) - association with emotional and behavioral problems in children - Eichler, Anna; Glaubitz, Katharina; Hartmann, Luisa Carla; Spangler, Gottfried (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2014)
Parental stress is increased in clinical contexts (e.g., child psychiatry) and correlates with behavioral and emotional problems of children. In addition, parental stress can result in a biased parental perception of child's behavior and emotions. These interrelations were examined in a normal (N = 320) and a clinical (N = 75) sample. The "Eltern-Belastungs-Screening zur Kindeswohlgefährdung" (EBSK; Deegener, Spangler, Körner & Becker, 2009) was used for the assessment of parental stress. As expected, increased EBSK scores were overrepresented in the clinical sample. In both samples stressed parents reported having children with more behavioral and emotional problems. Children of stressed parents in turn reported significantly less problems than their parents did. The rating of independent third persons, e.g. teachers, was not available and should be added in future research. Restrictions in methodology and conclusions for practice are discussed.
EVALuna2:23886

Das Eltern-Belastungs-Screening zur Kindeswohlgefährdung (EBSK) als Instrument zur kurz- und langfristigen Vorhersage des elterlichen Erziehungsverhaltens und der kindlichen Entwicklung - Glaubitz, Katharina (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2011)

Die Aussagekraft des Eltern-Belastungs-Screenings zur Kindeswohlgefährdung" (EBSK) in der Praxis - Eichler, Anna; Glaubitz, Katharina; Hartmann, Luisa Carla; Spangler, Gottfried (Kindesmisshandlung und -vernachlässigung, 2011)

Die Erfassung elterlicher Belastung mit dem Eltern-Belastungs-Screening zur Kindeswohlgefährdung (EBSK): Zusammenhänge zu Erlebens- und Verhaltensauffälligkeiten beim Kind - Eichler, Anna; Glaubitz, Katharina; Hartmann, Luisa Carla; Spangler, Gottfried (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2014)